Investigating the cytotoxic effect of aqueous extract of Peganum harmala on oxaliplatin-resistant HCT116 cell line and evaluating BAX gene expression - Zahra Salimizadeh; Sattar Tahmasebi Enferadi; Tayebeh Majidizadeh; Razieh Jalal; Frouzandeh Mahjoubi (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām)
Introduction:  Colorectal cancer is a prevalent digestive tract malignancy, with oxaliplatin being an effective chemotherapeutic drug, but long-term use can lead to drug resistance. It is crucial to develop methods to reduce CRC cells' oxaliplatin resistance. Peganum harmala L. (P. harmala), is a common anticancer treatment in traditional medicine. Materials & Methods: The study used P. harmala seeds extract to treat oxaliplatin-resistant HCT116 cells for 24 and 48 hours. Cell viability was determined using the MTT assay, and RNA extraction was performed from the treated and control cells. cDNA synthesis was performed using extracted RNAs, and the expression level of the BAX gene was analyzed using Real-Time PCR. Statistical analysis was conducted using Graph Pad Prism 8 software and t-test, with a significance level of P less than 0.05. Results: Findings indicated a significant correlation between the increase in the concentration of extract and the percentage of dead cells. The cytotoxicity of the aqueous extract of P. harmala seeds significantly increased from 24 to 48 hours in oxaliplatin-resistant HCT116 cells. Furthermore, a significant and considerable upregulation in the relative expression of the BAX gene was observed compared to the control group (P<0.001). Conclusion: The cytotoxic effect of the aqueous extract of P. harmala is dose- and time-dependent. The extract has the potential to induce apoptosis in colorectal cancer cells by regulating apoptosis-related genes, particularly by upregulating pro-apoptotic genes such as BAX.